Maternal Deprivation Increased Vulnerability to Depression in Adult Rats Through DRD2 Promoter Methylation in the Ventral Tegmental Area - Guo, Zhenli; Li, Shansi; Wu, Jialing; Zhu, Xiongzhao; Zhang, Yi (Frontiers in Psychiatry, 2022)
Objective: Early life adversity is a risk factor for depression in adulthood, however the underlying mechanisms are not well understood. This study is to investigate the effect of DNA methylation of DRD2 gene on early life stress-induced depression in adult rats. Methods: Newborn Sprague-Dawley rats were randomly assigned to four groups: maternal deprivation group (MD), chronic unpredictable stress (CUS) group, maternal deprivation plus chronic unpredictable stress (MD/CUS) group, and normal control group (NOR). Behaviors were measured by open field test (OPT), sucrose preference test (SPT) and forced swimming test (FST). Faecal CORT level was detected by ELISA. BiSulfte Amplicon sequencing PCR was used to assess methylation levels of DRD2 promoter. Results: CUS and MD/CUS rats had a significantly shorter total distance, longer immobility time, and higher CORT level, while MD and MD/CUS rats had a significantly lower percentage of central distance, more faeces, lower rate of sucrose preference, and lower DRD2 protein level in the VTA than NOR rats. CUS rats showed a significantly higher DRD2 mRNA and protein levels in the VTA than NOR rats. CUS, MD, and MD/CUS rats showed a significantly higher level of DRD2 promoter methylation than NOR rats. CORT level was significantly correlated with the sucrose preference rate in SPT, the immobility time in FST, the total distance and the number of fecal pellets in OPT. DRD2 protein level was significantly correlated with the sucrose preference rate and the number of fecal pellets. DRD2 mRNA level was significantly correlated with the percentage of central distance and the number of fecal pellets in OPT. The level of DRD2 promoter methylation was significantly correlated with the sucrose preference rate, immobility time, total distance, the percentage of central distance, and the number of fecal pellets. Conclusions: Early life MD increased vulnerability to stress-induced depressive-like behavior in adult rats. Enhanced DRD2 promoter methylation in the VTA maybe increase the susceptibility to depression.